Activity DPPH (1,1-diphenyl-2-picrylhidrazyl) free radical scavenging of some ready to drink teas on - Rohdiana, Dadan; Shabri, Shabri (Jurnal Penelitian Teh dan Kina, 2012)
Research of free radical scavenging activity of some ready to drink tea (RTD-Tea) was carried out. Generally, the result showed that tea beverages have a good of scavenging activity against DPPH free radical. T-AR was RTD-tea which has the stronger scaÂvenging activity against DPPH free radical. This RTD-tea has a low of EC50 value i.e. 63,55ml/ml. The scavenging activity followed were T-ES (63,95ml/ml), T-UP (65,75ml/ml), T-RO (86,85ml/ml), T-LI (91,15ml/ml), T-TA (107,53ml/ml), T-NG (125,36ml/ml) and T-AK (756,14ml/ml) respectively.